GAMBARAN PENGETAHUAN DAN SIKAP MENYIKAT GIGI PADA SISWA-SISWI DALAM MENCEGAH KARIES DI SDN 005 BUKIT KAPUR DUMAI - Ningsih, Susan Utari; Restuastuti, Tuti; Endriani, Rita (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCaries became one of the seriously medical problems for students especially for elementary school. Caries was demineralization of the tooth surface because of bacteria. This occured because of the deficiency of child knowledge for mouth and tooth healthy care. One kind of ways to took care of mouth and tooth healthy was to brushing teeth in an exact time and method. This study aim to described about knowledge and attitude to brushing teeth for students to prevent caries. This study has been done in SDN 005 Bukit Kapur Dumai with quantitative descriptive and cross sectional approchment. Samples for this study were students at IV, V and VI grade and amount of the samples at least 156 persons. The data was collected with interview using questionnaire. Based of the age there were (36,54%) at the age of 11 years old and female was (57,69%). The result of this study showed that most score for best knowledge grade was (69,87%) and positive attitude was (79,48%) and it was students at VI grade.Keywords : Knowledge, attitude, brushing teeth